Proceso contable y confiabilidad de la información financiera en el Comercial Disprifre de la ciudad de Babahoyo periodo 2020 - Zambrano Loor, Cecilia Del Carmen (2021)
The commercial "DISPRIFRE" is located in the city of Babahoyo whose main economic activity is the wholesale of various products for the consumer, starting its activities as a family business providing quality products for individual and wholesale consumption. The problem with this entity is that it does not have an adequate accounting process where it allows it to know the real financial results for decision-making, so the main objective is to design an accounting process that adapts to the needs of the entity so that it allows have reliability in your financial statements. The application of the initiative will allow greater control of its operations and performance of the entire financial part to improve its productivity and permanence in the market due to the fact that it is increasingly competitive in the sector, being an important part of competitors of the same activity economical. As a subline of investigation, “Financial, tax and social commitment management” was used, since in this it is proposed how businesses must register their accounting operations, keeping a control and verifying how reliable the financial information is so that the salesperson can achieve the objectives desired.